2011
DOI: 10.1159/000330419
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Substance P Levels in Patients with Persistent Cough

Abstract: Background: Substance P (SP) is involved in the pathogenesis of cough in animal models. However, few studies in humans have been reported and the roles of SP in clinical cough remain obscure. Objectives: To clarify the relevance of plasma levels of SP in patients with persistent cough. Methods: We studied 82 patients with cough persisting for at least 3 weeks and 15 healthy controls. Patients were classified as having asthmatic cough (cough-variant asthma and cough-predominant asthma; n = 61) or nonasthmatic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 98 publications
1
25
0
3
Order By: Relevance
“…We have also reported that plasma levels of substance P are elevated in patients with CVA and cough-predominant asthma as compared with healthy subjects [47]. cys-LTs induce the release of substance P through the stimulation of airway afferent nerve fibers [48], and LTRAs inhibit such release [48,49].…”
Section: Discussionmentioning
confidence: 99%
“…We have also reported that plasma levels of substance P are elevated in patients with CVA and cough-predominant asthma as compared with healthy subjects [47]. cys-LTs induce the release of substance P through the stimulation of airway afferent nerve fibers [48], and LTRAs inhibit such release [48,49].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, elevated SP levels were also found in the plasma (Otsuka et al, 2011) and nasal secretions (Cho et al, 2003) of patients with chronic cough. Indeed, it was postulated that elevated SP in nasal secretions defines a distinct population of patients with chronic cough, those with "upper airway cough syndrome" (Lim et al, 2011).…”
Section: B Transient Receptor Potential Channels Inmentioning
confidence: 94%
“…This correlates with increased levels of nitrosative stress, which enhances Substance P secretion [80]. Increased Substance P is also found in the plasma of chronic cough sufferers [81]. …”
Section: Reviewmentioning
confidence: 99%